Diagnosis of Focal Nodular Hyperplasia (FNH) after Liver Transplantation - Christina S. Gainey; Suzanne L. Palmer; Edward Mena; Navpreet Kaur; Yuna Gong; Jeffrey A. Kahn (Case Reports in Transplantation)
Following liver transplantation (LT), recipients can develop benign and malignant hepatic masses just like any other patient. Patients transplanted for hepatocellular carcinoma (HCC) undergo surveillance imaging, and any new mass seen on imaging must be carefully evaluated to rule out recurrent cancer. Focal nodular hyperplasia (FNH) is a benign tumor of the liver that most often occurs in women and is rarely symptomatic. It is important to distinguish FNH from more serious etiologies, such as recurrent HCC and other malignancies, since the treatments differ greatly. To date, there have been very few reports of FNH occurring in a liver allograft. We present a case of a patient with a history of a carcinoid tumor who underwent LT for HCC. Several years posttransplant, the patient was found to have a liver mass with classic features of HCC on imaging. The liver biopsy revealed the unexpected diagnosis of FNH. This finding avoided unnecessary treatment for HCC, which is associated with morbidity, especially in the posttransplant setting. We present our diagnostic approach, discuss the clinicopathologic and imaging findings of FNH, and review the literature on FNH in the posttransplant setting.